Medically Unexplained Oral Symptoms. (2nd April 2021) - Steel, Ben J; Goel, Vishal; Dorman, Paul J; Durham, Justin
Abstract : Medically unexplained symptoms (MUS) are common in all areas of healthcare, and when the term is applied to oral symptoms, it can be appropriately focused as medically unexplained oral symptoms (MUOS). This article reviews the causes/associations and presentations of MUOS in dentistry, and describes confusable or possible comorbid psychiatric conditions. Management of patients with MUOS in primary dental care often requires close working with the patient's GP and other professionals. Strategies for the assessment and management of such patients are described. CPD/Clinical Relevance: Dentists in primary care are likely to see patients with medically unexplained oral symptoms. A good knowledge of the correct identification and management of these symptoms is crucial for a satisfactory outcome. A proficiency in assessing and managing MUOS patients is an important skill for all primary care dentists.